A method for determining total iron content in solid waste samples by x-ray fluorescence spectrometry

CN116046826BActive Publication Date: 2026-10-23BEIJING SHOUGANG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310042535.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-28
Publication Date
2026-10-23
Estimated Expiration
2043-01-28

AI Technical Summary

Technical Problem

[0003]本申请提供了一种X-射线荧光光谱法测定固废样品中全铁含量的方法,以解决现有X-射线荧光光谱法测定固废样品中全铁含量分析结果准确度较差的技术问题

Benefits of technology

[0027]本申请实施例提供的该X-射线荧光光谱法测定固废样品中全铁含量的方法,通过钴粉并控制钴粉的配比,以钴作为内标,提高了测定固废样品中全铁含量的准确性。该方法还能同时测定所述固废样品中其他化学成分,如SiO2、CaO、MgO、Al2O3、TiO2、P。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116046826B_ABST
    Figure CN116046826B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of solid secondary resource sample detection, in particular to a method for determining the total iron content in a solid waste sample by X-ray fluorescence spectrometry. The method comprises the following steps: mixing cobalt powder and a fluxing agent with a solid waste sample to prepare a fusion sample; wherein the preparation ratio of the cobalt powder is controlled to be a set ratio; establishing an X-ray fluorescence spectrometer standard curve for the fusion sample by X-ray fluorescence spectrometry; and determining the total iron content in the solid waste sample according to the X-ray fluorescence spectrometer standard curve. The application solves the technical problem of poor accuracy of the analysis result of the total iron content in the solid waste sample determined by the existing X-ray fluorescence spectrometry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid secondary resource sample testing technology, and in particular to a method for determining the total iron content in solid waste samples by X-ray fluorescence spectrometry. Background Technology

[0002] To promote the comprehensive and efficient utilization of solid secondary resources and to conduct research on rotary kiln slag production processes, it is urgent to complete the testing of solid secondary resource samples. Currently, the acid dissolution-titanium trichloride reduction-potassium dichromate titration method is used to determine the total iron content, which directly pollutes the environment and has high recycling and disposal costs. Solid secondary resource samples have relatively high iron content, and excessively high fluorescence intensity causes the counter to miss the characteristic X-ray photoelectron count line, resulting in large fluctuations in the iron element fluorescence count rate and poor accuracy of the analytical results. Summary of the Invention

[0003] This application provides a method for determining the total iron content in solid waste samples by X-ray fluorescence spectrometry, in order to solve the technical problem that the accuracy of existing X-ray fluorescence spectrometry methods for determining the total iron content in solid waste samples is poor.

[0004] In a first aspect, this application provides a method for determining the total iron content in solid waste samples using X-ray fluorescence spectrometry, the method comprising the following steps:

[0005] Cobalt powder and flux are mixed with a solid waste sample to prepare a fused sheet sample; wherein the proportion of cobalt powder is controlled to a predetermined proportion.

[0006] A standard curve for X-ray fluorescence spectrometry was established for the fused sheet sample using X-ray fluorescence spectroscopy.

[0007] The total iron content in the solid waste sample was determined according to the standard curve of the X-ray fluorescence spectrometer.

[0008] Optionally, according to the method of claim 1, the cobalt powder comprises: lithium tetraborate, lithium metaborate, and cobalt trioxide; wherein,

[0009] The total weight M1 of the lithium tetraborate and the lithium metaborate satisfies the following relationship with the cobalt trioxide M2:

[0010] M1:M2 = 10:1.

[0011] Optionally, the chemical composition of the flux includes lithium tetraborate and lithium metaborate;

[0012] The weight ratio of lithium tetraborate to lithium metaborate is 67:33, 1:1, or 1:0.

[0013] Optionally, the flux weighs 7g and the cobalt powder weighs 0.5g.

[0014] Optionally, the solid waste sample may include at least one of the following: dry ash from ironmaking, gas ash, mixed material, OG fine sludge, fine ash, anhydrous sediment sludge, pipeline ash, kiln slag, and zinc oxide.

[0015] Optionally, before establishing the X-ray fluorescence spectrometer standard curve for the fused sheet using X-ray fluorescence spectroscopy, the method further includes:

[0016] Determine the analytical parameters of the X-ray fluorescence spectrometer corresponding to the determination of the total iron content to ensure the precision and accuracy of the sample analysis.

[0017] Optionally, the step of mixing cobalt powder and flux with a solid waste sample to prepare a fused sheet includes:

[0018] The solid waste sample was incinerated.

[0019] The flux and cobalt powder are mixed to obtain the first mixture;

[0020] The calcined solid waste sample was added to the first mixture and stirred to obtain a second mixture;

[0021] The second mixture is heated in stages to obtain molten sheets.

[0022] Optionally, the step of heating the second mixture in stages to obtain the molten sheet includes:

[0023] The second mixture is subjected to a first heating at a first set temperature.

[0024] Under a second set temperature, the second mixture after the first heating is subjected to a second heating to obtain a molten sheet.

[0025] Optionally, the first set temperature is 800℃-850℃; the second set temperature is 950-1050℃.

[0026] The technical solutions provided in this application have the following advantages compared with the prior art:

[0027] The method for determining the total iron content in solid waste samples using X-ray fluorescence spectrometry provided in this application improves the accuracy of determining the total iron content by using cobalt powder and controlling the proportion of cobalt powder, with cobalt as an internal standard. This method can also simultaneously determine other chemical components in the solid waste samples, such as SiO2, CaO, MgO, Al2O3, TiO2, and P. Attached Figure Description

[0028] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0029] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0030] Figure 1 This is a schematic flowchart of a method for determining the total iron content in solid waste samples by X-ray fluorescence spectrometry, provided as an embodiment of this application. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0032] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0033] In this application, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. Furthermore, in the description of this application, terms such as "comprising" and "including" mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships can exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be a single or multiple.

[0034] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0035] Firstly, this application provides a method for determining the total iron content in solid waste samples using X-ray fluorescence spectrometry. Please refer to [link to relevant documentation]. Figure 1 The method includes the following steps:

[0036] S1. Cobalt powder and flux are mixed with a solid waste sample to prepare a fused sheet sample; wherein the proportion of cobalt powder is controlled to a set proportion.

[0037] S2. Establish an X-ray fluorescence spectrometer standard curve for the fused sheet sample using X-ray fluorescence spectroscopy;

[0038] S3. Determine the total iron content in the solid waste sample according to the standard curve of the X-ray fluorescence spectrometer.

[0039] Glass fusion sample preparation is a sample preparation technique comparable to solution analysis in terms of uniformity. X-ray fluorescence spectrometry has a wide range of applications and fast sample analysis speed. However, there is currently no national standard method for analyzing total iron in solid waste samples using fusion sample preparation-X-ray fluorescence spectrometry. Due to the relatively high iron content in the sample, excessively high fluorescence intensity causes the counter to miss recording characteristic X-ray photoelectrons, resulting in large fluctuations in the iron fluorescence count rate and poor accuracy of the analysis results.

[0040] Secondly, manual chemical analysis is cumbersome, consumes a lot of manpower, has low testing efficiency, affects the pace of efficient production and testing, and cannot provide timely data support for production. The testing process generates chromium- and acidic chemical waste liquid, which is directly discharged and pollutes the environment, and has high recycling and disposal costs.

[0041] In this embodiment, cobalt powder is chosen to improve the accuracy of determining the total iron content in solid waste samples. The positive effects of cobalt powder are: cobalt and iron have similar properties; adding cobalt as an internal standard solves the problem of large fluctuations in total iron content analysis using X-ray fluorescence spectrometry.

[0042] This method can also simultaneously determine other chemical components in the solid waste sample, including SiO2, CaO, MgO, Al2O3, TiO2, and P. In existing technologies, analyzing solid waste samples is time-consuming and cannot achieve simultaneous fluorescence analysis of TFe, SiO2, CaO, MgO, Al2O3, TiO2, and P components using a single fused sample. This application provides an accurate and rapid fluorescence fusion analysis method for detecting TFe in secondary solid waste resource samples, combining oxidation with internal standard treatment to achieve simultaneous fluorescence analysis of TFe, SiO2, CaO, MgO, Al2O3, TiO2, and P using a single fused sample.

[0043] In some embodiments, according to claim 1, the cobalt powder comprises:

[0044] Lithium tetraborate, lithium metaborate, and cobalt trioxide; among which...

[0045] The total weight M1 of the lithium tetraborate and the lithium metaborate satisfies the following relationship with the cobalt trioxide M2:

[0046] M1:M2 = 10:1.

[0047] The positive effects of lithium tetraborate in cobalt powder include: acting as a flux to melt cobalt trioxide; the positive effects of lithium metaborate include: lowering the melting temperature, improving sample flowability, and enhancing the melting effect; and the positive effects of cobalt trioxide include: providing cobalt element for later internal standard use. The positive effect of controlling the total weight M1 of lithium tetraborate and lithium metaborate, and the cobalt trioxide M2, to be 10:1 is: it allows for complete melting of cobalt trioxide, provides a good internal standard effect during sample melting, and results in high precision of sample measurement results. If this ratio is not met, it can lead to poor uniformity in cobalt powder preparation or affect the precision of the final sample measurement results. In the embodiments of this application, the weight ratio of lithium tetraborate to lithium metaborate in the cobalt powder is 1:1, which has the positive effect of: reducing melting problems in solid waste secondary resource samples, increasing flowability, and enhancing the melting effect.

[0048] In some embodiments, the chemical composition of the flux includes lithium tetraborate and lithium metaborate;

[0049] The weight ratio of lithium tetraborate to lithium metaborate is 67:33, 1:1, or 1:0.

[0050] In this flux, the positive effects of lithium tetraborate are: it is mainly responsible for melting the sample; the positive effects of lithium metaborate are: it is responsible for melting the sample and, when mixed with lithium tetraborate, it lowers the melting temperature and improves the fluidity of the sample during the melting process.

[0051] The positive effects of controlling the weight ratio of lithium tetraborate to lithium metaborate to be 67:33, 1:1, or 1:0 are as follows: these ratios are all commonly used flux ratios and are commercially available; the preferred ratio is 1:1.

[0052] In some embodiments, the flux weighs 7g and the cobalt powder weighs 0.5g.

[0053] To improve the service life of the yellow platinum crucibles, relatively old yellow platinum crucibles discarded from the preparation of purchased samples were used for solid waste samples. These old crucibles resulted in a high cracking rate during sample preparation, requiring sample re-preparation, increasing analysis time, and reducing work efficiency. A flux addition of 7g was determined to thicken the sample while maintaining sample accuracy and precision, reducing the cracking rate from 30% to 0%. This solved the problem of frequent cracking and sample re-preparation when using old crucibles, further improving the service life of the yellow platinum crucibles. At this point, the cobalt powder addition was 0.5g.

[0054] In some embodiments, the solid waste sample includes at least one of the following: dry ash from ironmaking, gas ash, mixed material, OG fine sludge, fine ash, anhydrous sediment sludge, pipeline ash, kiln slag, and zinc oxide.

[0055] In the embodiments of this application, the selected solid waste samples are blast furnace slag, sintered ore, hematite, pellets, titanium concentrate, iron ore, and magnetite concentrate.

[0056] In some embodiments, before establishing an X-ray fluorescence spectrometer standard curve for the fused sheet using X-ray fluorescence spectroscopy, the method further includes:

[0057] Determine the analytical parameters of the X-ray fluorescence spectrometer corresponding to the determination of the total iron content to ensure the precision and accuracy of the sample analysis.

[0058] The analytical parameters of the X-ray fluorescence spectrometer used to determine the total iron content can be found in Table 1, as can the analytical parameters of the X-ray fluorescence spectrometer used to determine the contents of SiO2, CaO, MgO, Al2O3, TiO2, and P.

[0059] In some embodiments, the mixing of cobalt powder and flux with a solid waste sample to prepare a fused sheet includes:

[0060] The solid waste sample was incinerated.

[0061] The flux and cobalt powder are mixed to obtain the first mixture;

[0062] The calcined solid waste sample was added to the first mixture and stirred to obtain a second mixture;

[0063] The second mixture is heated in stages to obtain molten sheets.

[0064] In some embodiments, the step of heating the second mixture in stages to obtain the molten sheet includes:

[0065] The second mixture is subjected to a first heating at a first set temperature.

[0066] Under a second set temperature, the second mixture after the first heating is subjected to a second heating to obtain a molten sheet.

[0067] In some embodiments, the first set temperature is 800℃-850℃; the second set temperature is 950℃-1050℃.

[0068] The sample is first heated on a melting machine for oxidation, and the heating time is 5 minutes; the second heating is for melting, and the melting time is 5 minutes.

[0069] In the embodiments of this application, an oxidant and a release agent are also required during the heating and melting process; the oxidant can be lithium nitrate; the release agent can be ammonium iodide.

[0070] The "first set temperature" is the first heating temperature. The positive effects of controlling the first set temperature to 800℃-850℃ are: ensuring that the sample can be fully oxidized by the oxidant without reaching the melting point of the flux, and that the sample does not react with the flux.

[0071] If the temperature is too high, the sample may begin to melt before it is fully oxidized when the flux melting point is reached, increasing the risk of pot damage. If the temperature is too low, the oxidation effect may be insignificant, increasing the risk of pot damage later. The temperature can be 800℃ or 850℃.

[0072] The "second set temperature" refers to the second heating temperature. The positive effects of setting the second set temperature to 950℃-1050℃ are: ensuring that the sample can be completely melted and become a uniform and smooth sample piece; if the temperature is too high, it will affect the life of the flavonoid crucible to some extent; if the temperature is too low, it will cause the sample to melt incompletely to some extent, reducing the precision of the sample measurement; this temperature can be 950℃, 1000℃, or 1050℃.

[0073] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then general international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0074] Table 1. Instrument analysis parameters.

[0075] TFe Kα LiF200 0.25 FPC 50 50 <![CDATA[SiO2]]> Kα PET 0.60 FPC 50 50 CaO Kα LiF200 0.60 FPC 50 50 MgO Kα AX03 0.60 FPC 50 50 Al2O3 Kα PET 0.60 FPC 50 50 TiO2 Kα LiF200 0.25 FPC 50 50 P Kα GE111 0.60 FPC 50 50

[0076] Preparation of cobalt powder: Through experiments, the ratio of cobalt internal standard flux was determined to be 1:10. Cobalt powder was prepared by grinding the sample twice for 15 seconds at the first setting of a grinding machine. The powder was then placed into a pre-cleaned glass bottle, labeled, and ready for use.

[0077] Flux selection: Precision experiments were conducted on three fluxes: 67:33, 1:1, and 1:0 (lithium tetraborate: lithium metaborate). Two samples were selected, and each sample was analyzed five times at three levels. The precision was observed and is shown in Table 2.

[0078] Table 2 shows the precision of samples prepared with different fluxes.

[0079]

[0080]

[0081] The data shows that fluxes 67:33 and 1:1 have better precision, so this experiment chose flux 1:1.

[0082] Experimental steps:

[0083] Weigh approximately 1.5g of the sample and ignite it in a muffle furnace at 800℃ for 2 hours to fully oxidize the reducing substances and burn off the volatile substances. Weigh 7.0000g ± 0.0002g of mixed flux (1+1) into a crucible. Weigh 0.5000g ± 0.0002g of cobalt powder and mix the flux and cobalt powder evenly. Weigh 0.5000g ± 0.0002g of the ignited sample and place it in the center of the crucible without stirring. Weigh 0.4000g ± 0.0002g of lithium nitrate and cover the sample (stir gently on the surface, without touching the bottom of the crucible). Heat the sample at a low temperature of 800-850℃ for 5 minutes using a melting machine, then heat to 1000℃ and melt the sample for 5 minutes. Add ammonium iodide as needed based on the melting conditions. Establish the standard curve for X-ray fluorescence spectrometry.

[0084] Based on the content ranges of TFe, SiO2, CaO, MgO, Al2O3, TiO2, and P in the solid waste samples, standard samples were screened, and analytical curves were established. Since manganese interferes with iron determination, manganese ore standards with high manganese content were not selected for establishing the curves. The standard samples for establishing the analytical curves are shown in Table 3.

[0085] Table 3 shows the standard samples and their contents used to establish the analytical curve.

[0086]

[0087]

[0088] Correlation coefficients for each element in the curves were established: TFe curve correlation coefficient 0.999, SiO2 curve correlation coefficient 1.000, CaO curve correlation coefficient 1.000, MgO curve correlation coefficient 0.999, Al2O3 curve correlation coefficient 1.000, TiO2 curve correlation coefficient 0.998, and P curve correlation coefficient 0.999.

[0089] Accuracy verification

[0090] Seven batches of samples were compared using the original method and the new method. The experiment showed that the data for TFe, SiO2, CaO, MgO, Al2O3, TiO2, and P obtained by the new method were consistent with those of the original method, with no significant differences, and met the production requirements. The comparison results are shown in Table 4.

[0091] Table 4 Comparison results between the original method and the new method

[0092]

[0093] Using the original method as the standard, a comparison of the results between the original method and the new method shows that the X-ray fluorescence spectrometry method for determining the total iron content in solid waste samples provided in this application not only has high accuracy, but is also simple, time-saving, green, and pollution-free.

[0094] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for determining the total iron content in solid waste samples by X-ray fluorescence spectrometry, characterized in that, The method includes the following steps: Cobalt powder and flux were mixed with a solid waste sample to prepare a fused sheet sample; wherein the cobalt powder consisted of lithium tetraborate, lithium metaborate and cobalt trioxide, and the total weight M1 of lithium tetraborate and lithium metaborate and the cobalt trioxide M2 ​​were related by the ratio M1:M2=10:1, the weight of the flux was 7g, and the weight of the cobalt powder was 0.5g. A standard curve for X-ray fluorescence spectrometry was established for the fused sheet sample using X-ray fluorescence spectroscopy. The total iron content in the solid waste sample was determined according to the standard curve of the X-ray fluorescence spectrometer. The solid waste samples include at least one of the following: dry ash from ironmaking, gas ash, mixed material, OG fine sludge, fine ash, anhydrous sediment sludge, pipeline ash, kiln slag, and zinc oxide.

2. The method according to claim 1, characterized in that, The chemical composition of the flux includes lithium tetraborate and lithium metaborate; The weight ratio of lithium tetraborate to lithium metaborate is 67:33, 1:1, or 1:

0.

3. The method according to claim 1, characterized in that, Before establishing the X-ray fluorescence spectrometer standard curve for the fused sheet using X-ray fluorescence spectroscopy, the method further includes: Determine the analytical parameters of the X-ray fluorescence spectrometer corresponding to the determination of the total iron content to ensure the precision and accuracy of the sample analysis.

4. The method according to claim 1, characterized in that, The process of mixing cobalt powder and flux with a solid waste sample to prepare a fused sheet includes: The solid waste sample was incinerated. The flux and cobalt powder are mixed to obtain the first mixture; The calcined solid waste sample was added to the first mixture and stirred to obtain a second mixture; The second mixture is heated in stages to obtain molten sheets.

5. The method according to claim 4, characterized in that, The step of heating the second mixture in stages to obtain the molten sheet includes: The second mixture is subjected to a first heating at a first set temperature. Under a second set temperature, the second mixture after the first heating is subjected to a second heating to obtain a molten sheet.

6. The method according to claim 5, characterized in that, The first set temperature is 800℃-850℃; the second set temperature is 950℃-1050℃.